The impact of diurnal variations on emergence delirium following general anesthesia and surgery in children - Wei, Wei; Xie, Haihang; Xu, Yingyi; Qin, Jingwen; Guo, Xinying; Song, Xingrong; Yu, Gaofeng; Zhang, Na; Ma, Daqing; Tan, Yonghong; Zhao, Tianyun (Frontiers in Pediatrics, 2024)
Background Emergence delirium (ED) is a widely recognized issue that prolongs mechanical ventilation and post-anesthesia care unit (PACU) resuscitation time, consequently increasing hospital costs and mortality. Postoperative disturbance in circadian rhythms, commonly leading to sleep disorders, has been identified as a significant risk factor for ED. However, the influence of surgery timing (morning vs. afternoon) on the incidence of ED in pediatric patients undergoing general anesthesia remains unknown. Methods Patients aged 2–6 years who were operated on under general anesthesia with a bispectral index value between 50 and 60 were categorized based on anesthesia start time into either the morning surgery group (Group M, 8:00–12:00) or the afternoon surgery group (Group A, 13:00–17:00). The primary outcome was the post-extubation incidence of ED assessed by the Cornell Assessment of Pediatric Delirium (CAPD) score. Secondary outcomes included extubation time, duration of PACU stay, and adverse postoperative events and complications. Results We recruited a total of 560 patients, 280 in group M and 280 in group A. Compared to Group M, Group A exhibited a significantly higher incidence of ED (p < 0.001), elevated CAPD scores (p < 0.001), and prolonged PACU stays (p < 0.001). Notably, there was no significant difference in extubation time and anesthesia-related adverse events or other postoperative complications between the groups. Conclusion Our study highlights that the time of surgery significantly affects the incidence of ED, CAPD scores, and PACU stay duration in children. Further validation of these findings may guide future strategies to reduce ED.